Communication Strategy of BKMT Riau Management in the Development of Islamic Da'wah - Arwan Arwan; Abdullah Abdullah; Syukur Kholil (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
In implementing a communication strategy, a communication plan must include goals, objectives and steps. Likewise, the communication planning of the BKMT Riau Management in the development of Islamic Da'wah in the form of program activities. This study is conducted by using descriptive qualitative approach. The result shows that communication management in the development of Islamic Da'wah of BKMT Riau Management can be traced from the activities program of Da'wah and Issuance of BKMT Riau management for the 2012-2017 period, including planning for organizing, implementing and evaluating. The communication methods used by BKMT are more dominant in informative communication, persuasive communication and educational communication as the most effective and most used method.